Peningkatan Hasil Belajar Tematik Terpadu Siswa menggunakan Model Cooperative Learning Tipe Numbered Head Together di Kelas IV SD - Sintia Maharani; Tin Indrawati (Universitas Negeri Padang, 2022)
The purpose of this research is to describe the improvement student learning outcomes of integrated thematic learning by using Numbered Head Together model at Grade IV SDN 02 Tanjung Gadang Agam Regency. Type of the research is classroom action research by using qualitative and quantitative approach. The subjects of the research were teacher and 13 grade IV students. Therefore, the Numbered Head Togeteher model could improve the students learning outcomes of integrated thematic learning. The results of lesson plan observation on cycle I was 77.78%, and cycle II was 94.4%. The observation of teacher on cycle I was 79.16% and cycle II was 95.83%. While, the improvement of students aspect on cycle I was 79.16% and cycle II was 95.83%. While the average student learning outcomes in the knowledge aspect is 69.88 to 84.83, and in the skill aspect it gets an average of 67.78 to 94.67.